Management of circulatory failure after Fontan surgery - Kamsheh, Alicia M.; O’Connor, Matthew J.; Rossano, Joseph W. (Frontiers in Pediatrics, 2022)
With improvement in survival after Fontan surgery resulting in an increasing number of older survivors, there are more patients with a Fontan circulation experiencing circulatory failure each year. Fontan circulatory failure may have a number of underlying etiologies. Once Fontan failure manifests, prognosis is poor, with patient freedom from death or transplant at 10 years of only about 40%. Medical treatments used include traditional heart failure medications such as renin-angiotensin-aldosterone system blockers and beta-blockers, diuretics for symptomatic management, antiarrhythmics for rhythm control, and phosphodiesterase-5 inhibitors to decrease PVR and improve preload. These oral medical therapies are typically not very effective and have little data demonstrating benefit; if there are no surgical or catheter-based interventions to improve the Fontan circulation, patients with severe symptoms often require inotropic medications or mechanical circulatory support. Mechanical circulatory support benefits patients with ventricular dysfunction but may not be as useful in patients with other forms of Fontan failure. Transplant remains the definitive treatment for circulatory failure after Fontan, but patients with a Fontan circulation face many challenges both before and after transplant. There remains significant room and urgent need for improvement in the management and outcomes of patients with circulatory failure after Fontan surgery.